STUDY BALIAK NAGARI BALIAK KA SURAU AS LOCAL WISDOM IN KENAGARIAN KOTO TANGAH TILATANG KAMANG DISTRICT DISTRICT WEST SUMATRA AGAM - MELLYZA SUSANTI; WE. Tinambunan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Minangkabau is one of the ethnic groups and living in West Sumatra province, famous for its culture matrilinealnya (maternal lineage). Custom element, Nagari, and the ideology that Islam is not a simple blend in Minang people's lives. With this concept Minang society and see themselves and view the world. This is reflected in a very famous proverb Nagari namely: Indigenous basandi Syarak, Syarak basandi Qur'aan, Syarak Mangato, Indigenous mamakai, Natural Takambang so Teacher. The rapid development of science and advanced technology such as this, be the most important component in the social life of the community. This makes the government, traditional leaders, the elders and religious leaders wanted to reinstate a system of government that has begun bernagari forgotten because it is not running anymoreThis research uses descriptive qualitative method of data collection that was obtained based on the reality on the ground through observation, interviews, and documentation. Where the informant in the NAC board, community leaders, and the public. The informant obtained with snowbaal sampling technique with key informants niniak mamak.The results showed that baliak baliak ka ka village mosque is one of the ways in which local governments in order to crystallize the Minang culture is not lost and restore social life community like Minang rules when in reality not run properly due to lack of knowledge and communication to the public especially mamak niniak young people.Keyword: communication, Local wisdom,baliak ka nagari baliak ka surau